Data from manuscript "Reconciling equatorward migration of Southern Ocean fronts with minor Antarctic ice volume change during Miocene cooling" by Suning Hou and others ... - Hou, Suning (Zenodo, 2023)
Datasets published in the manuscript "Reconciling equatorward migration of Southern Ocean fronts with minor Antarctic ice volume change during Miocene cooling", currently in review. 5 datasets, all generated from ODP Site 1168, are submitted: data1 raw palynological counts data2 relative abundance of dinocyst ecogroups data3 dinocyst-based SST reconstructions data4 clumped isotope-based BWT reconstructions (raw clumped isotope data is deposited elsewhere) data5 benthic foraminifer stable isotope data Depth is plotted in meters below sea floor; sample depths are derived from the Ocean Drilling Program Age is in millions of years, calibrated to the Geologic Time Scale 2020. ...